Does the Burglar Also Disturb the Neighbor? Crime Spillovers on Individual Well-being - Daniel Avdic; Christian Bünnings (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2015)
Indirect psychological effects induced by crime are likely to contribute significantly to the total costs of crime beyond the financial costs of direct victimization. Using detailed crime statistics for the whole of Germany and linking them to individual-level mental health information from the German Socio-Economic Panel, we analyze whether local crime rates affect the mental health of residents. We estimate that a one standard deviation increase in local violent crime rates significantly decreases individual mental well-being among residents by, on average, one percent. Smaller effects are found for property and total crime rates. Results are insensitive to migration and not isolated to urban areas, but are rather driven by less densely populated regions. In contrast to previous literature on vulnerability to crime, we find that men, more educated and singles react more to variation in violent crime rates in their neighborhoods. One potential explanation could be that those who are more fearful of crime have developed better coping strategies and, hence, react less to changes in crime. – – Indirekte psychologische Effekte stellen möglicherweise einen erheblichen Teil der durch Kriminalität verursachten Gesamtkosten dar. Um zu analysieren, ob regionale Kriminalitätsraten die mentale Gesundheit beeinflussen, nutzen wir detaillierte Kriminalitätsinformationen für Deutschland und verknüpfen diese mit Informationen zu individueller mentaler Gesundheit aus dem Sozio-ökonomischen Panel. Unsere Schätzergebnisse implizieren, dass der Anstieg um eine Standardabweichung in der Gewaltverbrechensrate das mentale Wohlbefinden der lokalen Bevölkerung signifikant um durchschnittlich ein Prozent reduziert. Für Eigentumsdelikte und die Gesamtkriminalitätsrate beobachten wir geringere Effekte. Die Ergebnisse werden weder durch Wohnortwechsler beeinflusst noch sind sie auf urbane Regionen begrenzt, sondern sind vielmehr durch weniger dicht besiedelte Regionen getrieben. Im Gegensatz zur Literatur zur Angst vor Kriminalität beobachten wir, dass Männer, höher Gebildete und Alleinstehende sensibler auf Veränderungen in der regionalen Gewaltverbrechensrate reagieren. Eine Erklärung hierfür könnte sein, dass diejenigen, die mehr Angst vor Kriminalität haben, entsprechende Coping-Strategien entwickelt haben und daher auch weniger auf Veränderungen in der Kriminalitätsrate reagieren.
Keywords: C23; I18; K42; R23; 330; fear of crime; spillover effect; mental health; vulnerability; neighborhood effects; panel data